Kalimah Ma’alī al-Duktūr ‘Aḥmad Muḥamad ‘Alī Ra’īsa al-Binak al-‘Islāmī Liltanmīyya fi al-Mu’tamar al-Sādis li Wizrā‘I al-‘Auqāf wa al-Shu’ūn al-Islāmīyya bi Jakarta - Akhmad Muhammad Ali (Al-Jami'ah Research Centre, 1997)
Pidato: Kalimah Ma’alī al-Duktūr ‘Aḥmad Muḥamad ‘Alī Ra’īsa al-Binak al-‘Islāmī Liltanmīyya fi al-Mu’tamar al-Sādis li Wizrā‘I al-‘Auqāf wa al-Shu’ūn al-Islāmīyya bi Jakarta